Developing Games in Java™ - Vanhelsuwé, Laurence; Brackeen, David; Barker, Bret (New Riders, 2003)
If you already have Java programming experience and are looking to program games, this book is for you. David Brackeen, along with co-authors Bret Barker and Lawrence Vanhelsuwe, show you how to make fast, full-screen action games such as side scrollers and 3D shooters. Key features covered in this book include Java 2 game programming techniques, including latest 2D graphics and sound technologies, 3D graphics and scene management, path-finding and artificial intelligence, collision detection, game scripting using BeanShell, and multi-player game engine creation.